EFEKTIVITAS COOKIES KACANG KEDELAI TERHADAP PENURUNAN TEKANAN DARAH PADA SISWA MENENGAH ATAS - Puspitasari, Agitya; Susiloretni, Kun Aristiati (Poltekkes Kemenkes Semarang, 2016)
Background : Essential hypertension is the hypertension that is often experienced by adolescents (aged 13-18 years). Food sources of potassium has excellent potential to lower systolic and diastolic blood pressure. One of them is a soybean that has a potassium content of 1797 mg / 100 g which can be processed into cookies . Objectives : To determine the effectiveness of soy bean cookies to blood pressure in senior high school students of class X State 10 Semarang Method : The types of research is a true experimental Pre and Post Test Control Group Design. Number of subjects in the study of 20 persons. 10 persons the treatment group and 10 persons control group with a blood pressure of students who otherwise hypertension if ≥90 percentile according to age. This type of treatment given is the provision of a cookie soybean 100g a day , for 7 days. Statistical analysis used is anova repeated measure test. Result : In the treatment group there is a decrease in systolic and diastolic blood pressure before and after treatment has been controlled with potassium intake (p=0.000). A decrease in blood pressure after the administration of cookies soybeans is systolic blood pressure of 6.7 mmHg from 135.7 ± 5.16 mmHg to be 129± 4.94 mmHg and diastolic blood pressure 5 mmHg mmHg of 79.00±8.472 to be 75.00 ± 79.475 mmHg in the treatment group. Conclusion : There is a decrease in the effectiveness of blood pressure with soybean cookies s were statistically significant in Senior High School State 10 Semarang students hypertension. As an alternative choice of functional foods and effective in lowering blood pressure.